STRATEGIES TO DEVELOP STUDENTS CULTURAL UNDERSTANDING IN CLASSROOM - Asnur, Sardian Maharani (Elite : English and Literature Journal, 2016)
Teacher in a classroom sometimes are difficult to get the students' attention in order to comprehend the subject material since the students are coming from many different culture. This study aimed to give some strategies to develop students cultural understanding for remote area students. There are several strategies that proved to be effective to develop students cultural understanding in the classroom, those are use a variety of instructional strategies and learning activities; consider students' cultures and language skills when developing learning objectives ard instructional activities; objectives for affective and personal development; communicate orate expectations; provide rationales; provide frequent reviews of the content learned; facilitate independence in thinking and action; promote student on-task behavior, monitor students' academic progress during lessons and independent work; provide frequent feedback; require mastery. This study is far from comprehensive, as it only investigated the very surface of strategies to develop students cultural understanding in the classroom.